PENGETAHUAN, ILMU PENGETAHUAN DALAM FILSAFAT DAIN ISLAM - Samuji Samuji (Jurnal Paradigma, 2021)
To know and understand about knowledge, science in philosophy and Islam, the author deliberately raised the theme in writing this work in order to provide scientific research for writers and society in general. Knowledge as the initial process of knowledge exists. The process of science is included in the study of philosophical epistemology. Islam is a religion whose teachings are revealed by God to human society through the Prophet Muhammad SAW, as an Apostle in which he brings teachings that do not recognize one aspect, but various aspects of life, because in these teachings it involves issues of aqidah, shari'ah and morals. sourced from the Qur'an and Hadith. People who have knowledge and practice knowledge are called scientists. In Islam, this knowledge should be based on faith and piety because if in seeking knowledge it is not based on faith and piety, then the knowledge that we get will not produce knowledge that will benefit mankind and the universe.